2008
DOI: 10.1137/070681594
|View full text |Cite
|
Sign up to set email alerts
|

The Blasius Function: Computations Before Computers, the Value of Tricks, Undergraduate Projects, and Open Research Problems

Abstract: Abstract. The Blasius flow is the idealized flow of a viscous fluid past an infinitesimally thick, semiinfinite flat plate. The Blasius function is the solution to 2fxxxWe use this famous problem to illustrate several themes. First, although the flow solves a nonlinear partial differential equation (PDE), Toepfer successfully computed highly accurate numerical solutions in 1912. His secret was to combine a Runge-Kutta method for integrating an ordinary differential equation (ODE) initial value problem with som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 33 publications
4
69
0
Order By: Relevance
“…From equation it can also be shown that ψ=2d2fdη2, thus yielding ψ 0 = 2 κ , where the constant κ ≈ 0.322 is the second derivative of the Blasius function at the origin, d2f(0)/dη2. The value of κ is generally obtained by means of the well‐established noniterative Töpfer method [ Töpfer , ], and it was given to 16 digits precision by Boyd []. Further, in this work, we will improve this precision by a similar method.…”
Section: Estimation Of the Radius Of Convergence Through Complex‐planmentioning
confidence: 99%
See 1 more Smart Citation
“…From equation it can also be shown that ψ=2d2fdη2, thus yielding ψ 0 = 2 κ , where the constant κ ≈ 0.322 is the second derivative of the Blasius function at the origin, d2f(0)/dη2. The value of κ is generally obtained by means of the well‐established noniterative Töpfer method [ Töpfer , ], and it was given to 16 digits precision by Boyd []. Further, in this work, we will improve this precision by a similar method.…”
Section: Estimation Of the Radius Of Convergence Through Complex‐planmentioning
confidence: 99%
“…Figure presents |Ф( ζ )| in the complex plane. Notice that |Ф( ζ )| does not blow up in the region analyzed, which is different from the behavior of the complex‐valued Blasius function, which has poles in the complex plane [ Boyd , ].…”
Section: Estimation Of the Radius Of Convergence Through Complex‐planmentioning
confidence: 99%
“…Asaithambi [33] found this number correct to nine decimal positions as 0.332057336. In 2008, Boyd [34] reported 0.33205733621519630 as f (0) in the Blasius equation.…”
Section: The Blasius Problemmentioning
confidence: 99%
“…Very recently, Tajvidi et al [24] has used a modified rational Legendre method, to show that γ = 0.33209 with a 0.009% relative error. By the fourth-order Runge-Kutta method γ is determined γ «0.33205733621 5 19630, where all the sixteen decimal places are believed correct [8]. A fully analytical solution (i.e.…”
Section: Power Series Solutionsmentioning
confidence: 99%